Investigation of an Outbreak of Equine Herpesvirus-1 Myeloencephalopathy in a Population of Aged Working Equids - Nicola Pusterla; Kaila Lawton; Samantha Barnum; Kelly Ross; Kris Purcell (Viruses)
The objective of this study was to describe an outbreak of equine herpesvirus-1 myeloencephalopathy (EHM) in a population of aged equids. The outbreak was linked to the introduction of five healthy non-resident horses 15 days prior to the first case of acute recumbency. This fulminant EHM outbreak was predisposed by the grouping of the 33 unvaccinated animals in two large pens with shared water and feed troughs. Fourteen horses (42.4%) developed neurological deficits within the first week of the outbreak. Four additional equids developed fever and respiratory signs (EHV-1 infection), while fifteen horses remained healthy. EHM was supported by the detection of EHV-1 N752 in blood (n = 11) and/or nasal secretions (9). Three out of four equids with EHV-1 infection and two out of fifteen healthy horses tested qPCR-positive for EHV-1. All animals were managed in the field. EHM and EHV-1 equids were treated with a combination of antiherpetic, anti-inflammatory, and antithrombotic drugs. Six out of fourteen EHM horses (42.9%) were euthanized because of recumbence and the inability to stand with assistance or vestibular signs. Anti-EHV-1 total IgG and IgG 4/7 levels in acute serum samples showed no significant difference amongst the three disease groups (p > 0.05); however, antibody levels rose significantly between acute and convalescent serum samples for EHM (p = 0.0001) and EHV-1 equids (p = 0.02). This outbreak highlights a very high EHM attack and fatality rate in a population of aged equids and rapid spread of EHV-1, as the population shared common pens and feeding practices. The outbreak also showed that EHM cases can be managed in the field when referral to a hospital is not an option.